1997
DOI: 10.1200/jco.1997.15.10.3208
|View full text |Cite
|
Sign up to set email alerts
|

Revertant and potentiating activity of lonidamine in patients with ovarian cancer previously treated with platinum.

Abstract: The 37% response rate observed in this study (28% in refractory or early-relapsed patients), suggests that the synergism between CDDP and LND observed in vitro against ovarian cancer cell lines can be clinically confirmed. However, larger series and randomized studies are needed to assess definitely the revertant activity of LND on CDDP-refractory patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…This finding was confirmed in most of the primary cultures from clinical human lung cancer tumour we used, which represents an important step in validating preclinical results before translating them into clinical practice (Villa et al, 1992). The results from the present study reinforce the importance, previously evidenced for other drugs and tumour types (Citro et al, 1991;Savini et al, 1992;Dogliotti et al, 1996;De Lena et al, 1997;Silvestrini et al, 1997;Amadori et al, 1998;Fischel et al 1998;Van Moorsel et al 1998Zoli et al, 1999) of preclinical research to define the best treatment scheduling. Considering the recently published results (Spiridonidis et al, 1998;Georgoulias et al, 1999), which show that gemcitabine and docetaxel can be safely used in combination, a protocol on advanced NSCLC will shortly be activated in Italy based on the findings from the present study.…”
Section: Discussionsupporting
confidence: 84%
“…This finding was confirmed in most of the primary cultures from clinical human lung cancer tumour we used, which represents an important step in validating preclinical results before translating them into clinical practice (Villa et al, 1992). The results from the present study reinforce the importance, previously evidenced for other drugs and tumour types (Citro et al, 1991;Savini et al, 1992;Dogliotti et al, 1996;De Lena et al, 1997;Silvestrini et al, 1997;Amadori et al, 1998;Fischel et al 1998;Van Moorsel et al 1998Zoli et al, 1999) of preclinical research to define the best treatment scheduling. Considering the recently published results (Spiridonidis et al, 1998;Georgoulias et al, 1999), which show that gemcitabine and docetaxel can be safely used in combination, a protocol on advanced NSCLC will shortly be activated in Italy based on the findings from the present study.…”
Section: Discussionsupporting
confidence: 84%
“…In one study, high lonidamine serum levels were found one hour after administration (50) and further suggested a possible synergistic effect of lonidamine and the CDDP combination. This conclusion was also suggested by De Lena et al (48). However, they also characterized the incidence of hematological side effects and found that patients subjected to the treatment experienced anemia, leukopenia, and thrombocytopenia.…”
Section: Lonidaminethe Clinical Experience In Anticancer Treatmentsupporting
confidence: 71%
“…This conclusion was also suggested by De Lena et al . . However, they also characterized the incidence of hematological side effects and found that patients subjected to the treatment experienced anemia, leukopenia, and thrombocytopenia.…”
Section: Glycolysis‐inhibiting Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…An enhanced antioxidant capacity allows cancer cells to not a universal finding, and mitochondrial respiration impairment is not a fixed feature of cancer cells [41] . Although the glycolytic inhibitors targeting the Warburg effect have been investigated in various cancer types, the glycolytic inhibitors with the exception of 3-BP (a lactate analog) [18,19, , 3-BrOP (a 3-bromopyruvate derivative) [71][72][73][74] , and dichloroacetate (DCA) have demonstrated low efficacy in arresting tumor growth when used alone [99] ; these inhibitors include 2-deoxy-D-glucose (a glucose analog) [70,[100][101][102][103][104][105][106][107][108][109][110][111][112] , lonidamine (a derivative of indazole-3-carboxylic acid) [113][114][115][116][117][118][119][120][121][122][123][124][125][126][127][128][129][130][131][132] , methyl jasmonate on HK , 3-(3-pyridinyl)-1-(4-pyridinyl)-2-propen-1-one on PFK [162]…”
Section: Initiation Of Metastasismentioning
confidence: 99%